The Impact of the Russia–Ukraine War on the Stock Market. Evidence from the U.S. Defense and Logistics Industries - Andrii, Nadtochii (My University, 2026)
This study examines the impact of the Russian invasion of Ukraine on the stock market performance by conducting an event study with a specific focus on the defense and logistics industries. By utilizing an event study methodology, abnormal returns are calculated over estimation, anticipation and event windows across different model specifications, including the constant return model, the market-adjusted model, and the Capital Asset Pricing Model (CAPM). The results show that the invasion itself did not lead to a strong immediate market reaction on the event day but consequently generated significant abnormal returns during the post-event adjustment period. The defense sector experienced positive abnormal returns, reflecting expectations of increased military spending, while the logistics sector showed negative anticipation effects followed by strong positive recovery. The findings suggest that U.S. financial markets do not fully in-corporate information from major geopolitical events instantaneously, not completely confirming the Efficient Market Hypothesis. Furthermore, the results highlight significant sectoral differences in market responses, emphasizing the importance of industry-specific analysis for the event studies of crisis outbreak.
Keywords: Russian invasion of Ukraine 2022; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance